Teachers Implementation of Deep Learning in ELT: An Activity Theory Perspective - Marcellino Eka Putra; Najmi Laila Sani; Sabrina Sabrina; Dadan Nugraha; Haryanti Haryanti (Universitas Cokroaminoto Palopo, 2026)
The objective of this study is to seek the challenges experienced by English teachers in applying deep learning, focusing on their classroom experiences and perceptions using the activity theory as a framework that focuses on its concepts of contradiction, boundary objects, and boundary crossing. This study used a semi-structure interview to understand the three participants' experiences as teachers in implementing Deep Learning in the classroom practices. Key challenges to their implementation came in the form: limited understanding, workload and time constraints, implementation barrier, limited administrative preparation, curriculum adaptation gap, and government requirement. However, the participants were able to overcome the challenges that arose by treating it as a connecting tool to connect their teaching methods. These findings raise important theoretical and practical issues related to strategies for overcoming challenges encountered in implementing deep learning, as implemented by the participants by institutional support and teachers training, implementation experience, facility support, and fellow teachers support. One of the connections is understanding how teachers manage the challenges they encounter by connecting their various activity systems as objects to overcome the obstacles that occur in the deep learning implementation system they use in the classroom.